Compulsory and voluntary admissions in comparison: A 9-year long observational study. (December 2022) - Draghetti, Stefano; Alberti, Siegfried; Borgiani, Gianluca; Panariello, Fabio; De Ronchi, Diana; Atti, Anna Rita
Background: Few studies, so far, have been specifically designed to highlight the features related to Compulsory Admissions (CA) and Voluntary Admissions (VA) in Italian psychiatric emergency wards. Aims: The main purpose of this observational study was to compare the sociodemographic and clinical characteristics of VA and CA and to explore possible predictors of re-admissions. Methods: During a 6-month Index Period (February, the 1st–July, the 31st 2008) all psychiatric admissions were documented and then followed-up through all available informatic systems for the next 9 years. Results: Out of 390 hospitalizations, 101 (25.9%) were compulsory (CA rate was 2.79 per 10, 000 inhabitants per year, mean duration of hospitalizations of 7.33 ± 7.84 days). Diagnoses were recorded for the 325 patients who had been hospitalized during index period: schizophrenic psychoses ([ p = .042], in particular schizophrenia [ p = .027]), manic episode ( p = .044), and delusional disorders ( p = .009) were associated with CA; conversely, the diagnosis of unipolar major depression ( p = .005) and personality disorders ( p = .048) were significantly more frequent in VA. The 325 admitted patients were followed up for 1, 801 person-years. No significant differences were found in terms of drop-outs, transferring, and discharge rates, and mortality rates due to both natural causes and suicides. Factors associated with at least one compulsory readmission were younger age and having had a previous CA ( p = .011); conversely having been engaged with psychiatric services for over 1 year prior to index hospitalization was protective for a subsequent CA ( p = .013). Conclusions: After a 40-year old political reform, the current study shows that, in a context of integrated outpatient and inpatient services, engagement with outpatient care may be protective for compulsory rehospitalization.